2014
DOI: 10.11114/jets.v2i2.331
|View full text |Cite
|
Sign up to set email alerts
|

Learning Style Preferences of Undergraduate Dietetics, Athletic Training, and Exercise Science Students

Abstract: The study assessed the preferred learning style (LS) of college students and compared LS preferences among students majoring in Dietetics, Exercise Science, and Athletic Training. LS questionnaires were distributed to students (N=693, mean age 20.5±1.7) enrolled in health science courses at three Midwestern universities. Most students preferred a converger LS followed by assimilator, accommodator, and diverger. Some students preferred a combination of two LS. Chi square results indicated a significant relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…In the light of this study based on its general objective, it was found that there is a relationship between the learning style and the learning context, which is necessary for the educational process (WALLS, 2005;BRECKLER;JOUN;NGO, 2008;TOMULETIU et al, 2011;KHADEMI;MOTALLEBZADEH, 2013;LEE;KIM, 2014;WAGNER et al, 2014;ÇOLAK, 2015;ÖZDEMIR, 2016).…”
Section: Discussionmentioning
confidence: 96%
“…In the light of this study based on its general objective, it was found that there is a relationship between the learning style and the learning context, which is necessary for the educational process (WALLS, 2005;BRECKLER;JOUN;NGO, 2008;TOMULETIU et al, 2011;KHADEMI;MOTALLEBZADEH, 2013;LEE;KIM, 2014;WAGNER et al, 2014;ÇOLAK, 2015;ÖZDEMIR, 2016).…”
Section: Discussionmentioning
confidence: 96%
“…Por ejemplo la teoría del Aprendizaje Experiencial de David Kolb (1981Kolb ( , 1999, aunque muy utilizada para identificar y describir los EA en poblaciones con características diferentes (Brown y otros, 2008;Gurpinar, Bati y Tetik, 2011;Wagner, Hansen, Rhee, Brunt, Terbizan y Christensen, 2014), se basa en interpretaciones que han sido modificadas y revisadas en varias ocasiones, hasta la publicación de la Versión 3 que se utiliza en el presente estudio. El modelo propuesto por el autor, consta de un ciclo de aprendizaje que se produce en dos dimensiones y define cuatro etapas o tipos de aprendizaje: la percepción de los contenidos a aprender a través de la experiencia concreta de los conocimientos o bien mediante la conceptualización abstracta de estos y el procesamiento del contenido a través de la experimentación activa o mediante la observación reflexiva.…”
unclassified